Outdoor Exposure Effects on Different Formulated Clear Coats of Wood as Sustainable Urban Design Material - Sahin, Candan Kus; Merdan, Rahim (European Journal of Applied Sciences, 2025)
When wood is exposed to the outdoors, degradation can occur either in the coatings or the wood surface, or in both materials. However, interaction between exposure radiation and the wood surface produces complex photooxidation reactions that degrade the clear film and appear as discoloration. There are very complicated variations found for the changes in all three-color coordinates in terms of outdoor exposure impact on modifications of seven different coatings and exposure directions. However, the similar surface coatings on tangent and radial surfaces respond differently when exposed to outdoor. The varnish+teak oil and plant oil+teak oil (ΔEEr: 3.47 vs. ΔEFr: 8.65) coated samples show higher radial surface discolorations than counterpart tangent surfaces, while tangent surfaces show higher discoloration than radial surfaces for the other five transparent coated samples. The most stable surface against outdoor exposure was found with a radial surface of varnish+enamel treatment of ΔECr: 1.71 (metric), followed by radial and tangent surface of varnish+teak oil treatments (ΔEEr: 2.78 and ΔEEt: 3.47). It is notable that all discolorations were perceptible to the human eye (ΔE:>1.0 unit) when look carefully. There is no trend observed for chroma and hues of samples. Solely varnish coated (hBt) and plant oil+varnish coated (hGt) samples show considerably shifts of color for tangent surfaces and solely varnish coated (hBr) and plant oil+ varnish coated (hFr) samples for radial surfaces (Δh ± >5 degree), while all other samples do not show noticeable differences between radial and tangent surfaces of coated samples, either weathered or not, and those changes were not perceptible by the human eye.